Seasonality and criteria for concession of water in the Ivinhema basin (Research, Society and Development, 2020)
Global demand for water has been increasing per year due to population growth, economic development, and changes in consumption patterns, among other factors. This increase in water demand is expected to continue in the next decades. The objective of this work was to evaluate the use of different criteria to grant the use of water from the Ivinhema river basin, Brazil. Monthly periods were compared to annual periods to calculate the reference flows Q7,10 and Q95. The relative differences in water availability using different reference flow rates for water concession were quantified. The replacement of the annual criteria (standard in Brazil) for water concession by 50% of monthly Q7,10 and 70% of monthly Q95 can potentially increase the use and improve the management of water resources. The best criteria to award grants is the monthly Q7,10, which despite being more restrictive, it allows higher flow rates when there is excess water, and lower rates in the months of low water availability.